Glacial and periglacial geomorphology of the Drang Drung, Haskira, and Pensilungpa glaciers, Trans-Himalayan Ladakh, India - Shahid Younis Bhat; Emma-Louise Cooper; Levan G. Tielidze; Irfan Rashid; Andrew N. Mackintosh (Journal of Maps)
Glacial geomorphological mapping is vital for understanding the role of glaciers in shaping landscapes, as well as glacier response to climate change. We present a glacial geomorphological map of the Drang Drung, Haskira, and Pensilungpa glaciers in Trans-Himalayan Ladakh, India. Mapping was conducted using a combination of high-resolution satellite imagery (Pléiades, SPOT, Planet) supplemented with Google Earth Pro and a 2 m resolution Pléiades Digital Surface Model (DSM). Our map provides a detailed inventory of glaciers and glacial landforms (see Main map), including over 12,000 features across a ∼320 km² area. Mapped features include landforms such as moraines, alluvial fans, flutes, rock glaciers, crevasses, and debris cones. The map was validated by carrying out extensive ground truthing in 2023 and 2024. The main map is projected at a 1:33,000 scale, and is designed to be utilised by glaciologists and geomorphologists to understand glacier dynamics, date landforms, and trace glacier evolution, while also helping mountaineers to plan safe routes.